Technology Innovation Of Organic Waste Decomposition In Providing Feedstuffs - Prawirodigdo, S.; Utomo, B. (Indonesian Bulletin of Animal and Veterinary Sciences, 2011)
Previous investigations in Indonesia indicated that an inactive ovary was a chronically reproduction problem in ruminants. There was a tendency that nutrition deficiency inhibited ovulation, oestrus occurrence, and conception in ruminants. Obviously, there is a correlation between sufficient nutrient consumption and reproduction performance of such animals. Thus, application of the production/reproduction technology innovation for improving ruminantâs productivity in the villages needs to be supported by the availability of sufficient feed. Whilst, there is a competition among ruminants in fulfilling feed requirement. On the other hand, there are large amounts of organic waste of food and plantation estate industries which are potential for non-traditional feedstuffs. The examples of such organic wastes are: 4,817,630 ton dry matter (DM) of cacao pod, 314,042.51 ton DM of coffee pulp and hulls, and 29,700,000 ton DM of palm frond, leaves and trunks. Unfortunately, such materials contain anti-nutritive substance. Nevertheless, technology innovation for decomposing organic waste is available and its validity has been proven to be satisfactory and appropriate. Regarding the limitation of feedstuffs, introduction of technology innovation for organic waste decomposition to provide feed for improving livestock productivity is promising to be applied. Key words: Decomposition technology, organic waste, productivity, ruminants